2021
DOI: 10.19173/irrodl.v22i1.4970
|View full text |Cite
|
Sign up to set email alerts
|

Using Open Educational Resources at Viterbo University: Faculty and Student Feedback

Abstract: This study evaluated a coordinated and collaborative pilot implementation of open educational resources (OER) across multiple disciplines including nursing, accounting, environmental science, religious studies, and finance. Participating faculty were qualitatively surveyed regarding their experience creating and implementing OER in a course. Students were surveyed on their perceptions of OER quality, cost savings, and ease of use. Faculty had an overall positive experience with OER, believing there was a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Various challenges have been reported in this study, such as copyright issues or legal barriers, low quality of OERs, lack of awareness, lack of time among creators and users, lack of skills, lack of technical infrastructure and inadequate organizational support. However, the major challenge identified in most of the studies was lack of time to find relevant resources (Hassall and Lewis, 2017; Henderson and Ostashewski, 2018; Mikroyannidis and Papastilianou, 2021; Oelfke et al , 2021; Pande, 2018; Shams et al , 2020; Tang, 2020; Tlili et al , 2020). Further, sometimes students go for easy and quick choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various challenges have been reported in this study, such as copyright issues or legal barriers, low quality of OERs, lack of awareness, lack of time among creators and users, lack of skills, lack of technical infrastructure and inadequate organizational support. However, the major challenge identified in most of the studies was lack of time to find relevant resources (Hassall and Lewis, 2017; Henderson and Ostashewski, 2018; Mikroyannidis and Papastilianou, 2021; Oelfke et al , 2021; Pande, 2018; Shams et al , 2020; Tang, 2020; Tlili et al , 2020). Further, sometimes students go for easy and quick choices.…”
Section: Discussionmentioning
confidence: 99%
“…Among all selected 21 studies, 17 studies reported that OERs are free of cost and time-saving that expand access to learning, and allow the students anywhere in the world to access OERs at any time and access the material repeatedly. Therefore, one of the most compelling reasons for using OERs is lowering or eliminating the costs of course materials (Bansal et al , 2013; Belikov and Bodily, 2016; Kinskey et al , 2018; KreljaKurelovic, 2016; Kumar et al , 2021; Moore and Reinsfelder, 2020; Oelfke et al , 2021; Pounds and Bostock, 2019; Tang, 2020; Thomas, 2017; Wright et al , 2019).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation